(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Nephrotic syndrome (NS) is a chronic renal pathology, classified into steroid sensitive (SSNS) or steroid resistant (SRNS) groups based on response to corticosteroids. Treatment of choice in pediatric NS is always corticosteroid. Steroid resistant nephrotic syndrome in paediatric patients may account for 20 to 30 % of total NS cases and it is significant concern for paediatricians. Steroid resistant cases are difficult to treat and have higher risk of development of end stage renal disease. A case control study was conducted among 48 children suffering from nephrotic syndrome, aged 2–12 years. Among them, 36 patient showed sensitivity to steroid treatment and 12 showed resistance. Haematological markers (haemoglobin, haematocrit, RBC count) and biochemical markers (albumin, proteinuria, urea, creatinine) were compared. Clinical features (anaemia, hypertension, severity of enema) were also compared. Independent t-tests and chi square tests were used for determining statistical significance (p < 0.05 was considered significant). Haemoglobin was significantly decreased in SRNS patients (p = 0.0002). RBC count, haematocrit, albumin were reduced in SRNS but not statistically significant. Proteinuria was significantly higher in SRNS (p = 0.001). Presence of hypertension and severity of edema was statistically significant among the case and control groups (p<0.001). SRNS patients showed much reduced haemoglobin and albumin values with more proteinuria than SSNS patients. The findings accentuate the relevance of prompt identification and focused therapy in SRNS. Resistance to steroid has poorer prognosis as significant glomerular damage may injure their kidney and overall health outcomes.